Association Between Food and Drug Administration Approval and Disparities in Immunotherapy Use Among Patients With Cancer in the US - Ermer, Theresa; Canavan, Maureen E.; Maduka, Richard C.; Li, Andrew X.; Salazar, Michelle C.; Kaminski, Michael F.; Pichert, Matthew D.; Zhan, Peter L.; Mase, Vincent; Kluger, Harriet; Boffa, Daniel J. (JAMA Network Open, 2022)
IMPORTANCE Clinical trials and compassionate use agreements provide selected patients with access to potentially life-saving treatments before approval by the Food and Drug Administration (FDA). Approval from the FDA decreases a number of access barriers; however, it is unknown whether FDA approval is associated with increases in the equitable use of novel therapies and reductions in disparities in use among patients with cancer in the US.
CRIS-Team WoS Importer:2022-07-15